The interaction between oxidative stress and Schwann cells - Sihan Yang; Zijun Zhang; Qing Liao; Qipeng Ouyang; Yongyou Ye; Wei Lu; Zhendong Jiang (Experimental Biology and Medicine, 2026)
After peripheral nerve injury (PNI), a moderate increase in reactive oxygen species (ROS) levels can promote the proliferation and differentiation of Schwann cells (SCs) and participate in signal transduction. However, excessive ROS can trigger oxidative stress, and its harmful effects can overshadow the beneficial ones, such as inducing apoptosis, activating inflammation, disrupting environmental stability, and severely hindering neural processes. Therefore, if the damage caused by oxidative stress to SCs can be effectively alleviated, it will provide a new approach for the precise regeneration between peripheral nerves and target organs, thereby reducing the complications of PNI. With the advancements in materials science and neural tissue engineering, functional and precisely designed neural scaffolds and conduits have emerged as highly promising therapeutic strategies. This article focuses on revealing the interaction between SCs and oxidative stress during nerve injury, as well as the innovative tissue engineering technologies and new paradigms for damage repair that have emerged based on this interaction. It aims to provide effective new methods for addressing temporary or permanent functional impairments of PNI/peripheral neuropathies.